Ventilatory efficiency during ramp exercise in relation to age and sex in a healthy Japanese population. Issue 1 (January 2021) - Ashikaga, Kohei; Itoh, Haruki; Maeda, Tomoko; Itoh, Hidetaka; Ichikawa, Yuri; Tanaka, Shiori; Ajisaka, Ryuichi; Koike, Akira; Makita, Shigeru; Omiya, Kazuto; Kato, Yuko; Adachi, Hitoshi; et al.
Highlights: Reference values of ventilator efficiency variables in a normal Japanese population. Cardiopulmonary exercise testing was performed using a cycle ergometer. Tidal volume and minute ventilation (V̇E) during ramp exercise testing were evaluated. Slope of V̇E versus carbon dioxide (V̇E vs. V̇CO2 slope), minimum V̇E/V̇CO2, and oxygen uptake efficiency slope were also determined. Abstract: Background: The current understanding of ventilator efficiency variables during ramp exercise testing in the normal Japanese population is insufficient, and the responses of tidal volume (VT) and minute ventilation (V̇E) to the ramp exercise test in the normal Japanese population are not known. Methods: A total of 529 healthy Japanese subjects aged 20–78 years underwent cardiopulmonary exercise testing using a cycle ergometer with ramp protocols. VT and V̇E at rest, at anaerobic threshold, and at peak exercise were determined. The slope of V̇E versus carbon dioxide (V̇CO2 ) (V̇E vs. V̇CO2 slope), minimum V̇E/V̇CO2, and oxygen uptake efficiency slope (OUES) were determined. Results: For males and females in their 20 s, peak VT (VTpeak) was 2192 ± 376 and 1509 ± 260 mL ( p < 0.001), peak V̇E (V̇Epeak) was 80.6 ± 18.7 and 57.7 ± 13.9 L/min (sex differences p < 0.001), the V̇E vs. V̇CO2 slope was 24.4 ± 3.2 and 25.7 ± 3.2 ( p = 0.035), the minimum V̇E/V̇CO2 was 24.2 ± 2.3 and 27.0 ± 2.8 ( p < 0.001), and the OUES was 2452 ± 519 and 1991 ± 315 ( p < 0.001), respectively. VTpeak and V̇Epeak decreased with age and increased with weight and height. The V̇E vs. V̇CO2 slope and minimum V̇E/V̇CO2 increased with age, while conversely, the OUES decreased with age. Conclusions: We have established the normal range of VT and V̇E responses, the V̇E vs. V̇CO2 slope, the minimum V̇E/V̇CO2, and the OUES for a healthy Japanese population. Some of these parameters were influenced by weight, height, sex, and age. These results provide useful reference values for interpreting the results of cardiopulmonary exercise testing in cardiac patients.